El juego-trabajo y su importancia en el desarrollo del lenguaje oral de los niños y niñas de 3 a 4 años, del jardín de infantes Adela Pinargote de la parroquia de Chillogallo de la ciudad de Quito, período lectivo 2013 – 2014. Lineamientos alternativos - Grijalva Caiza, Tatiana Elizabeth (2014)
The investigation Project is: THE GAME-WORK AND ITS IMPORTANCE IN 3 TO 4 YEARS OLD CHILDREN ORAL LANGUAGE DEVELOPMENT "ADELA PINARGOTE" BEGINNING SCHOOL CHILLOGALLO PARISH QUITO CITY SCHOOL PERIOD 2013-2014. The General objective was to increase through the play-work the development in 3 to 4 years old children oral language development "Adela Pinargote" beginning school Chillogallo parish Quito city school period 2013-2014. The methods and techniques used were: The Scientific, inductive, deductive, Analytical - Synthetic , descriptive methods and the statistical model, the same as served to identify, describe, interpret and analyze the problem raised in the techniques and instruments consist: The teachers and parents Survey to learn about the use of the game - work in your daily hours of work; and, an Observation guide to monitoring to assess the children oral language development. With the application of the survey one determined that 45 % of the teachers use the game - work as a methodological strategy in its daily work day, With the application of parents surveys to determined that 38 % stimulates the oral language, they Always reached a scale valorativa of and 68 % reached a scale valorativa of sometimes. With the application of the observation guide determined that 43 % of children express their feelings, knowing and thoughts, they Always obtained a scale valorativa of 57 % reached an evaluation of sometimes.